Ikonografija i simbolizam podnog mozaika glavnog broda južne bazilike u Caričinom gradu - OGNJEVIĆ, Tamara (Leskovački zbornik, 2007)
In a triple-naved basilica with a transept, in the southern section of the lower part of Caričin Grad (Iustiniana Prima), figural, floral and geometric mosaics discovered during 1949-1950. The mosaics of the central nave on the left (northern), lunar zone in the naos, presents 18 fields with various motifs, among which amazonomachy and centauromachy, lunar and chthonic symbols. Presentations of horses and predators from the feline species (lynx or mountain lion) also have lunar symbolism, as well as the figures of a bull and cow in the northern zone of the mosaic, connected with storms and the Moon. The images are encircled by a larger rectangle with a presentation of a hunter piercing, not killing - but chasing away a female bear with a cub - representing the triumph of faith over sin (female bear) and the fruits of sin (cub). On the south side - a hunter killing a lion, symbolizes the victory of true faith. In the image of the lion, the author sees a solar beast, a direct incarnation of the Sun. This figure is separated by an ambo from the field showing a shepherd (priest) who is driving three sheep. The lunar-solar symbolism of the mosaic is considered unique by the author, which has no parallel among the mosaics of the early Christian period and, in the programme sense, is not similar to the mosaic in the Church of Saint Demetrios in Nicopolis, with which it has been compared.
p. 49-72, 13 ill. n.b., résumé en anglais, p. 69-72 : « The iconography and symbolism of the floor mosaic of the main nave of the Caričin Grad south basilica ».
Keywords: Bibliographie par pays, région ou ensemble géographique; Amazonomachie; Ambon; Basilique (Caričin Grad, SRB); Berger; Brebis; Centauromachie; Chasse (scène de); Chasseur; Cheval; Décor figuré; Décor géométrique; Décor végétal; Église (Nikopolis, GRC) S.Demetrios; Fauve; Iconographie; Iconologie; Lune, lunaire; Ours, ourson; Panneau; Rectangle; Symbole, symbolisme; Taureau; Vache; Lion; Programme (décoratif, figuratif); Lynx; Caričin Grad; Nicopolis d'Épire